The Effect of International Marketing and Tariff and Non-Tariff Strategy to Business Performance through Nationalism Spirit - Riwayadi, Eko; Murti, Tri Hesti; Monoarfa, Maya; Tahjoo, Anastina; Waisapi, Jeffry Yulianto; Young, Felina C (Jurnal Multidisiplin Madani, 2024)
In the rapidly evolving landscape of global business, this research investigates the intricate interplay between international marketing, tariff and non-tariff strategies, nationalist spirit, and their collective impact on business performance. Employing a cross-sectional quantitative design within the Indonesian context, the study explores how businesses adapt their marketing approaches to navigate diverse trade regulations and respond to nationalist sentiments. The results reveal significant relationships between international marketing and both business performance and nationalist spirit. Moreover, the study underscores the substantial influence of tariff and non-tariff strategies on business performance, with pronounced effects in markets characterized by heightened nationalist spirit. These findings contribute to theoretical advancements in international business literature and offer practical insights for businesses aiming to formulate effective strategies, navigate regulatory complexities, and enhance performance in a globalized economy